The diverted dream : community colleges and the promise of educational opportunity in America, 1900-1985 - Brint, Steven G. (OUP E-Books., 1989)
A history of community colleges in America; examines the shift of emphasis from liberal-arts transfer courses to terminal vocational programs and the implications of this for upward mobility.